(untitled) (Engrami, 2022)
The closing-in phenomenon occurs when a drawing is reproduced close to or superimposed on the original model. This phenomenon is classically understood as a type of constructional apraxia that occurs during graphomotor copying tasks or gestural imitations. Its manifestation on neuropsychological tests is taken as a neurocognitive indicator of dementia, most often as an indicator of Alzheimer’s disease. Although a highly specific sign for this dementia type, current literature suggests that it is certainly not pathognomonic for Alzheimer’s dementia, but occurs in a wide range of neurocognitive disorders with or without dementia. Although the Serbian academic circles are familiar with this phenomenon, thus far it hasn’t been sistematically explored. For this reason, in addition to discussing the significance of this phenomenon in clinical practice, in this paper we also summarize and critically analyze current knowledge regarding closing-in phenomenon. In this paper we discuss: (1) Historical development and conceptualization; (2) Neuroanatomical correlates of the phenomenon; (3) Compensation hypothesis; (4) Attraction hypothesis.